2021
DOI: 10.3390/cancers13092239
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Chemotherapy Modulates Clonal Interactions to Prevent Drug Resistance in Non-Small Cell Lung Cancer

Abstract: Despite recent advances in deciphering cancer drug resistance mechanisms, relapse is a widely observed phenomenon in advanced cancers, mainly due to intratumor clonal heterogeneity. How tumor clones progress and impact each other remains elusive. In this study, we developed 2D and 3D non-small cell lung cancer co-culture systems and defined a phenomenological mathematical model to better understand clone dynamics. Our results demonstrated that the drug-sensitive clones inhibit the proliferation of the drug-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…To comply with the 3-R rule, we used supernumerary mice (aged 12 weeks) that were destined to be sacrificed. A spheroid formed from DsRed-expressing MB cells [ 50 , 51 ] was then grafted onto each cerebellum slice. These organotypic co-culture models were placed on inserts and maintained as previously described [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…To comply with the 3-R rule, we used supernumerary mice (aged 12 weeks) that were destined to be sacrificed. A spheroid formed from DsRed-expressing MB cells [ 50 , 51 ] was then grafted onto each cerebellum slice. These organotypic co-culture models were placed on inserts and maintained as previously described [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, they develop more slowly compared to the MTD regimen, which could be due to the multimodal character of the former [20,48]. In this regard, it has been demonstrated that MC modulates the balance of drug-resistant and drug-sensitive clones co-existing within a tumor better than an MTD regimen [49]. Cancer cells and host cells develop tumor support mechanisms to escape therapy.…”
Section: Metronomic Chemotherapy: a Multimodal Therapymentioning
confidence: 99%
“…They reported the biologically optimal dose as a periodically increasing dose titration. Recently, a theoretical study by Ledzewicz 28 and another in vitro study by Bondarenko et al 29 also reported a biologically optimal dose 5 to reduce resistance. However, all existing literature addresses the issue of the optimal dose in theoretical or experimental settings.…”
Section: Introductionmentioning
confidence: 98%